1.
∫ dx\[(x*)(2+x)]=1/2*∫ dx*[(1/x-1/(2+x)]=1/2[lnx-ln(2+x)]+C
2.
∫ e^(2x)*sin3xdx
=-1/3e^(2x)cos3x+2/3∫ e^(2x)*cos3xdx
=-1/3e^(2x)cos3x+2/9 e^(2x)*sin3x-4/9∫ e^(2x)*sin3xdx
所以
13/9*∫ e^(2x)*sin3xdx=-1/3e^(2x)cos3x+2/9 e^(2x)*sin3x=1/9*e^(2x)*(2sin3x-3cos3x)
∫ e^(2x)*sin3xdx=1/13*e^(2x)*(2sin3x-3cos3x)
希望对你有所帮助
如有问题,可以追问。
谢谢采纳
祝学习进步
∫ dx\[(x*)(2+x)]
1/[x(2+x)] =1/2[1/x-1/(x+2)]
原式=∫1/2[1/x-1/(x+2)] dx
=1/2ln|x|-1/2ln|x+2|+C
∫ e^2x*sin3x dx
∫ e^(2x)sin3x dx
= (- 1/3)∫ e^(2x) dcos3x
= (- 1/3)e^(2x)cos3x + (1/3)(2)∫ e^(2x)cos3x dx <=分部积分
= (- 1/3)e^(2x)cos3x + (2/3)(1/3)∫ e^(2x) dsin3x
= (- 1/3)e^(2x)cos3x + (2/9)e^(2x)sin3x - (2/9)(2)∫ e^(2x)sin3x dx <=分部积分
(1 + 4/9)∫ e^(3x)sin3x dx = (2/9)e^(2x)sin3x - (1/3)e^(2x)cos3x
∫ e^(3x)sin3x dx = (9/13)[(2/9)e^(2x)sin3x - (1/3)e^(2x)cos3x] + C
==> ∫ e^(3x)sin3x dx = (1/13)(2sin3x - 3cos3x)e^(2x) + C
∫ dx\[(x)*(2+x)] = ∫ 1/2 [1/x - 1/(2+x)] dx =1/2 [ lnx -ln(2+x)] +C